Szyk przestawny a struktura wersu Jana Kochanowskiego - Senderska, Joanna (Stylistyka, 1996)
It is assumed that so-called accomodations, which are components of language system, are responsible for adapting the system to the text. Stylistic accomodations, which adapt definite type of style for the needs of the text, accompany textual accomodations. However, they are secondary in relation to the textual ones. Therefore, stylistic accomodations can modify adapted components of language system, causing a lot of deviations from grammar rules in literary texts (See: T.Skubalanka, 1991). Some stylistic accomodations seem to be responsible for the usage of verse patterns which could be treated as a part of a hypothetical stylistic system. Thus, metrical systems are capable of generating poetic texts. Versification rules, which form the verse system, have an effect on grammar rules. That seems to be the main reason for many deviations from acceptable word order’ in Jan Kochanowski’s poetry. This article deals with particular kind of inversion which causes nominal and adverbial phrases to become discontinuous, i.e. certain words which do not belong to these phrases are between their immediate constituents. Basic components of syllabic verse, such as constant number of syllables in the line, rhyme, expressional pause and even metre, which seems to occur in Kochanowski’s poetry, could be the Teason for this type of construction. O f course there are some constructions which cannot be justified by mles of any metrical system. However, this fact seems not to exclude the model in which linguistic and stylistic phenomena are closely related to each other.